2014
DOI: 10.1080/10643389.2013.829768
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Mathematical Modelling of Aerobic Plug Flow and Nonideal Flow Reactors: A Critical and Historical Review

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Modelling is a widely acknowledged tool for fundamental understanding, design and optimization of wastewater treatment processes (van . Reviews on wastewater treatment models have generally focussed on either anaerobic (Batstone et al, 2015, Liotta et al, 2015, Sadino-Riquelme et al, 2018, Tomei et al, 2009 or aerobic processes (Hauduc et al, 2013, Karpinska and Bridgeman, 2016, Liotta et al, 2014, because these require different redox conditions. Except for Nicolella et al (2000), Liu and Tay (2004) and Milferstedt et al (2017a), reviews focussing on granular sludge have discussed anaerobic (Chong et al, 2012, Saravanan and Sreekrishnan, 2006, Schmidt and Ahring, 1996 and aerobic processes (Bengtsson et al, 2018, Ni and Yu, 2010a, Winkler et al, 2018 separately as well.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Modelling is a widely acknowledged tool for fundamental understanding, design and optimization of wastewater treatment processes (van . Reviews on wastewater treatment models have generally focussed on either anaerobic (Batstone et al, 2015, Liotta et al, 2015, Sadino-Riquelme et al, 2018, Tomei et al, 2009 or aerobic processes (Hauduc et al, 2013, Karpinska and Bridgeman, 2016, Liotta et al, 2014, because these require different redox conditions. Except for Nicolella et al (2000), Liu and Tay (2004) and Milferstedt et al (2017a), reviews focussing on granular sludge have discussed anaerobic (Chong et al, 2012, Saravanan and Sreekrishnan, 2006, Schmidt and Ahring, 1996 and aerobic processes (Bengtsson et al, 2018, Ni and Yu, 2010a, Winkler et al, 2018 separately as well.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…However, if these basic models are combined in reactor networks, it is possible to describe the behaviour of a real unit operation, including effects such as dead zones, nonideal back mixing, and/or bypassing effects. This approach is not limited to pharmaceutical processes, but is also utilised, for example, in chemical reaction engineering and modelling of water treatment processes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several mathematical models have been used to describe hydrodynamics when modeling liquidphase bioreactors performance, from plug flow or complete mixed ideal models to computational fluid dynamic (CFD) models [2]. These authors compared performance-prediction models of the most common aerobic bioreactors, considering ideal and non-ideal flows, and concluded that CFD models are the most complete because they allow us to describe space-time evolution of physical and biological phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…These authors compared performance-prediction models of the most common aerobic bioreactors, considering ideal and non-ideal flows, and concluded that CFD models are the most complete because they allow us to describe space-time evolution of physical and biological phenomena. Therefore, CFD techniques have been employed as a useful tool for understanding hydrodynamics and biochemical reactions in wastewater treatment field [2][3][4][5][6], where the bioreaction behavior is associated to the liquid phase dynamics. Biofilms mathematical modeling has been well-established by IWA Task Group on Biofilm Modeling [7], describing the basic features to model biofilms, developing numerous mathematical models in different dimensions and defining a set of benchmark problems to evaluate model responsiveness under established scenarios [8].…”
Section: Introductionmentioning
confidence: 99%